2010
DOI: 10.1111/j.2040-1124.2010.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant type 1 diabetes mellitus associated with a reactivation of Epstein–Barr virus that developed in the course of chemotherapy of multiple myeloma

Abstract: A 70‐year‐old woman who was diagnosed with multiple myeloma underwent chemotherapy. Three months after beginning chemotherapy, she was readmitted to the hospital because of fever and hepatopathy. Her elevated Epstein–Barr virus (EBV) antibody levels showed that the hepatopathy was caused by reactivation of EBV. On the 18th hospital day, the levels of fasting plasma glucose (FPG; 451 mg/dL) and pancreatic enzymes were suddenly elevated. Elevation of HbA1c level (6.4%) was slight, as compared with that of the FP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Our patient presented with fever and fatigue without any other symptoms before developing FT1D, and the Coxsackie A2 virus infection was confirmed serologically. Table 2 summarizes the reported cases in which virus infection was proven to be involved in the development of FT 1D (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). These cases include adults of both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient presented with fever and fatigue without any other symptoms before developing FT1D, and the Coxsackie A2 virus infection was confirmed serologically. Table 2 summarizes the reported cases in which virus infection was proven to be involved in the development of FT 1D (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). These cases include adults of both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…EBV is present in more than 90% of the population and the decreased ability of the immune system to control/eliminate EBV infection may be responsible for causing EBV-associated diseases ( 35 , 54 ) such as rheumatoid arthritis ( 34 , 55 , 56 ), systemic lupus erythematosus ( 34 , 57 , 58 ), Sjögren’s syndrome ( 34 ), multiple sclerosis ( 59 61 ), myasthenia gravis ( 62 ), diabetes mellitus type 1 ( 53 ), fulminant type diabetes ( 63 ), celiac disease ( 64 ), autoimmune thyroiditis ( 65 , 66 ), Hodgkin and non-Hodgkin lymphoma ( 35 , 67 ) ( Supplemental Table 2 ).…”
Section: Immunopathobiology Of the Epstein-barr Virusmentioning
confidence: 99%
“…Similarly, most studies reported no increase in EBV viral load in patients with ME/CFS ( 84 , 111 ). If this is due to the fact that the possible trigger of some EBV-associated diseases are the EBV-latent cells rather than viral load ( 34 , 35 , 43 , 63 , 66 , 67 , 112 114 ), remains unknown in ME/CFS. Thus, to our knowledge, there is scarce evidence based in prospective cohort studies, describing rates and associations with post-infective fatigue syndrome (i.e., ME/CFS) following proven acute EBV.…”
Section: A Hypothetical Association Between Ebv and Me/cfsmentioning
confidence: 99%
“…The sudden and complete destruction of pancreatic β-cells is thought to be a cause of this disease, but the precise mechanisms of such cell destruction remain unclear. It has been suggested that viral infections, such as reactivation of human herpes virus-6, Epstein-Barr virus, cytomegalovirus, coxsackievirus, mumps virus, and influenza type B virus, are related to the onset of FT1DM [16][17][18][19][20][21][22]. In this study, 86.7% of patients presented with signs suggestive of a preceding viral infection.…”
Section: Discussionmentioning
confidence: 59%